Rancang Kontruksi Saluran Udara Tegangan Menengah (SUTM) 20 KV Di Desa Tanjung Kasri Kecamatan Jangkat Kabupaten Merangin Provinsi Jambi - Susilo, Dede Tri J; Dewi, Rozlinda; Suprapto, Eko; Djufri, S. Umar (Universitas Batanghari Jambi, 2023)
Construction design and electricity distribution planning cannot be separated from how the electricity distribution system is built. Moreover, electricity is an important factor in creating a just and prosperous society in all fields. This research analyzes the design of the 20 KV Medium Voltage Air Line (SUTM) in the Tanjung Kaasri Village location, Angkan District, Merangin Regency, Jambi Province, whether it is in accordance with the standards used by PLN (SPLN). The research method used is the method of observation and measurement in the field. The results of the research concluded that when calculating the mechanical force of the pole, a 12 meter, 200 daN iron pole and a 9 meter, 100 daN iron pole were chosen as the schor pole. Then the use of TM poles includes: TM-1 Number of 45 rods, TM-3 Number of 80 rods, TM-4 And the cable used is AAAC-S 150 mm with a total number of cables of 22,240 The calculation results and the realization in the field are almost close, the difference is only under 1%. By always carrying out evaluations on each project, this data can be used as input for project owners and implementers, so that the quality and reliability of the system can be met.